2015
DOI: 10.1016/j.cell.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Integration Landscape during Latent and Active Infection

Abstract: SUMMARY The barrier to curing HIV-1 is thought to reside primarily in CD4+ T cells containing silent proviruses. To characterize these latently infected cells, we studied the integration profile of HIV-1 in viremic progressors, individuals receiving antiretroviral therapy, and viremic controllers. Clonally expanded T cells represented the majority of all integrations and increased during therapy. However, none of the 75 expanded T cell clones assayed contained intact virus. In contrast, the cells bearing singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
467
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(529 citation statements)
references
References 39 publications
49
467
3
1
Order By: Relevance
“…Archived proviral integration site analysis provided further support for clonal expansion of infected T cells (8,24,25). In all cases examined, a large proportion of the archived integrated proviruses were found to belong to expanded clones of CD4 + T cells that T1 T2 T1 T2 T1 T2 T1 T2 58% 11% 58% 32% share a unique integration site.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Archived proviral integration site analysis provided further support for clonal expansion of infected T cells (8,24,25). In all cases examined, a large proportion of the archived integrated proviruses were found to belong to expanded clones of CD4 + T cells that T1 T2 T1 T2 T1 T2 T1 T2 58% 11% 58% 32% share a unique integration site.…”
Section: Discussionmentioning
confidence: 78%
“…One of the challenges in studying the reservoir is that the majority (>90%) of integrated proviruses in CD4 + T-cell DNA are defective and cannot produce infectious virions (6)(7)(8)(9). Comparatively few cells harbor the replication-competent proviruses that constitute the clinically relevant reservoir, and there are currently no markers to distinguish these cells from those cells bearing defective proviruses.…”
mentioning
confidence: 99%
“…The in vivo presence of clonally expanded proviral populations has been reported by ourselves and others (14,(23)(24)(25)(26). However, there is minimal evidence for transcription of defective proviruses (14,27).…”
Section: Significancementioning
confidence: 67%
“…p24-negative wells were also negative by an assay for HIV-1 RNA (Roche Taqman v2.0). Infectious units per million (IUPM) were calculated using maximum likelihood estimate (5,9). (C) HIV-1 sequences obtained from the p24-positive wells on day 21, as indicated by the symbols, were obtained by bulk sequencing of the p6-RT region and subjected to neighbor-joining phylogenetic analysis.…”
Section: Significancementioning
confidence: 99%
“…It has been suggested that CD4 + T-cell clones are not likely to contain replication-competent HIV-1 because expression of viral proteins is cytotoxic, and the host's immune system would preferentially eliminate infected cells that express viral proteins (4). Only a small proportion of integrated proviruses are intact (4), and it has been proposed that clonally expanded CD4 + T cells contain only defective proviruses and that intact proviruses that make up the reservoir are found only in unexpanded cells (5). Previous studies have reported that populations of virus with identical sequences emerge in the plasma after several years of suppressive cART (6, 7), but it is not known whether the identical viruses found in the blood of patients are infectious.…”
mentioning
confidence: 99%